2007
DOI: 10.1073/pnas.0611226104
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive climatic molecular evolution in wild barley at the Isa defense locus

Abstract: Wild barley (Hordeum spontaneum) represents a significant genetic resource for crop improvement in barley (Hordeum vulgare) and for the study of the evolution and domestication of plant populations. The Isa gene from barley has a putative role in plant defense. This gene encodes a bifunctional ␣-amylase/subtilisin inhibitor that inhibits the bacterial serine protease subtilisin, fungal xylanase, and the plant's own ␣-amylase. The inhibition of plant ␣-amylases suggests this protein may also be important for gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
56
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 33 publications
(37 reference statements)
2
56
0
Order By: Relevance
“…Comparing the recent studies of the stress-induced genes Dhn1 (Yang et al, 2009) and Dhn6 (Yang et al, 2011), hsp17 has higher divergences, while the disease resistance-related gene Isa had fewer polymorphisms (Cronin et al, 2007). The ECI model provides clues to future evolutionary studies on both stress genes and speciation genes.…”
Section: Model Of the Eci Is Valuable To Study The Local Gene Adaptationmentioning
confidence: 92%
See 1 more Smart Citation
“…Comparing the recent studies of the stress-induced genes Dhn1 (Yang et al, 2009) and Dhn6 (Yang et al, 2011), hsp17 has higher divergences, while the disease resistance-related gene Isa had fewer polymorphisms (Cronin et al, 2007). The ECI model provides clues to future evolutionary studies on both stress genes and speciation genes.…”
Section: Model Of the Eci Is Valuable To Study The Local Gene Adaptationmentioning
confidence: 92%
“…Wild barley, H. spontaneum, was selected as a major model organism at EC because it is a highly inbreed species (Nevo, 1992). Based on the physiological and molecular population genetic studies of wild barley (Nevo et al, 1997;Cronin et al, 2007), we found that H. spontaneum at EC displays dramatic interslope adaptive genomic divergence, slope-specific fitness components, and incipient sympatric speciation on the opposite slopes (Nevo, 2009;Yang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…BASI belongs to the proteinase inhibitor class of plant pathogenesisrelated proteins (13), which inhibits proteins excreted by a range of pathogens during the infection/attack process. Diversity within the Isa locus in wild barley populations growing in differing environments is correlated with climatic differences, and populations from drier environments have greater diversity compared with populations growing in relatively wetter environments (14). Diversity at the Isa locus, especially diversity predicted to change the amino acid sequence, is likely to be significant in plant disease defense.…”
mentioning
confidence: 99%
“…Given the role of these genes at the interface of plant and environment, diversity within defense genes is of key interest to the study of molecular evolution. In this study, we have assessed the genetic diversity in additional plant defense genes [Rpg1, ABC1037, Adh1, betaine aldehyde dehydrogenase 1 (BADH1), and BADH2] with functional mechanisms that differ from the mechanisms of Isa in the wild barley populations studied in the work by Cronin et al (14) to (i) compare the overall genetic diversity of these genes within identical samples from ecogeographically diverse wild populations and (ii) assess whether diversity was associated with ecogeographic variables in these populations within a broader range of plant defense genes.…”
mentioning
confidence: 99%
“…Among the few adaptive genes identified in other organisms to date, several show patterns consistent with the recruitment of alternative alleles at highly variable genes. For instance, loci involved in the parallel reduction of body spines in sticklebacks (Chan et al 2009), crypsis in insects (Reed et al 2011) and vertebrates (Rosenblum and Harmon 2010), as well as genes associated to plant host-pathogen interactions (Caicedo et al 1999;Rose et al 2004;Cronin et al 2007) and flowering time differences (Johanson 2000;Subramaniam and Rausher 2000;Zufall and Rausher 2004;Cooley et al 2011;Smith and Rausher 2011), have been recurrently targeted by selection and are highly variable across the species ranges. In general, these results may arise from selection on recurrent mutations or on old variants present as standing variation .…”
Section: Evidence For the Repeated Recruitment Of Adaptive Variantsmentioning
confidence: 99%